Host-natural enemy communities in a changing world: The impact of forest loss on cavity-nesting Hymenoptera and their natural enemies - Queiros, C. N.; de Deus, J. P. A. [UNESP]; Dias, A. M. P.; Buschini, M. L. T. (FapUNIFESP (SciELO), 2025)
Cavity-nesting bees and wasps provide important ecosystem services for humans. This study aimed to understand how the replacement of forests with non-forest habitats affects the structure and interaction network of cavity-nesting bees, wasps, and their natural enemies. From 1,536 trap-nests distributed across 48 sites, we collected a total of 541 built nests, from which 1,420 hosts and 254 natural enemies emerged. We found no significant differences in species abundance, richness, or diversity between forest and matrix environments. However, abundance evenness was higher in forests. Interestingly, host species composition differed between forests and matrix areas, while natural enemy composition remained similar. Similarly, network metrics did not differ significantly between the two environments. Despite this apparent resistance of cavity-nesting hymenopteran communities to forest loss, many species are highly specialized in utilizing wooded areas and are not adapted to other environments. As a result, we risk losing not only specific and rare species but also their unique ecological functions. We emphasize the need to include these forest-dependent species in more conservation plans, as most remain poorly studied, from basic aspects of their natural history to applied research on their ecological functions and economic relevance. Future studies should also investigate the potential unseen effects of host composition shifts and the increased dominance of certain species in matrix areas on biodiversity patterns. This could provide clearer insights for improving conservation and management strategies.